The Immunological Response in Rabbits to Carrageenans, Sulphated Galactans Extracted from Marine Algae - Johnston, Kenneth Harper (My University, 1968)
Carrageenan, a mixture of sulphated galactans extractable by hot water from certain marine algae, has been known for its activity in a reversible stimulation of connective tissue growth. One subcutaneous injection of this polysaccharide elicits a granuloma formation which regresses after a few weeks. A single injection after regression results in heightened response; this suggested an immunological reaction. Serial injections of either lambda or kappa carrageenan into rabbits resulted in the formation of precipitins. The present study gives both qualitative and quantitative studies of the reaction involved. Fractions of carrageenans from different species of marine algae were tested for their ability to precipitate either anti-lambda carrageenan antiserum or anti-kappa carrageenan antiserum. Deductions were made from the data as to the structure of the polysaccharides.
Keywords: immunological, rabbits, sulphated, galactans, marine, tissue, growth, structure